Five-Finger Hypnosis and Murottal Therapy to Prevent Preeclampsia in Pregnant Women - Hasnah Hasnah; Ilhamsyah Ilhamsyah; Darti Darti; Wahdaniah Wahdaniah; Nurul Fadhilah Gani; Nurhidayah Nurhidayah (Al-Sihah : The Public Health Science Journal, 2023)
The incidence of preeclampsia in Indonesia for the Southeast Asian continent is relatively high, with roughly 190 per 100,000 live births. According to the World Health Organization (WHO), the condition accounts for 12% of maternal deaths. Therefore, this study aimed to investigate the effectiveness of Five-Finger hypnosis and murottal therapy in stabilizing blood pressure, pulse, respiration, and activating endorphins. The study employed a quantitative method, specifically a quasi-experimental one-group pre and post-test design. Univariate data analysis was conducted to examine the characteristics of the sample, including age, education, and parity, and the Wilcoxon test was employed as the statistical test. The results showed that pregnant women were at risk of developing preeclampsia, as indicated by the age, education level, and parity of 9, 14, and 24 pregnant women. Furthermore, a significant difference was observed between the pretest and posttest, with an average decrease in blood pressure ranging from 2 to 6 mmHg (p=0.000). This result study provided that five-Finger hypnosis intervention and murottal therapy were effective in preventing preeclampsia. Consequently, the study strongly recommended the dissemination of the Five-Finger and murottal hypnotic intervention modules to a wider population as a preventive measure against preeclampsia.